ALQURAN DAN TAFSIR DALAM PERSPEKTIF TASAWUF - Mursalin Ilyas (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2018)
This article elaborated the posision of Quran and it exegecis in Tasawuf perspective. The research questions were how the essential of the Quran in Tasawuf perspective, and what kind of the exegecis method was used in that perpective. Collecting data based on library research, especially about Sufi’s saying on the essential of Word of God and their comments on the Quran. Analysing the data based on tafsir and tasawuf approach. The finding research showed that Word of God was a part of the attribute of God as a part of His self (dhat) in the first time; and the Quran that was received by Muhammad peace be upon him was as signified of Word of God. The Tasawuf perspective on the meaning of the Quran consist of two kinds, i.e. revealed the essential meaning of the Quran and brought out the meaning to be a guidance for the spiritual seeker (salik) to obtain Knowledge of God (ma’rifatullah).